1969
DOI: 10.1079/bjn19690014
|View full text |Cite
|
Sign up to set email alerts
|

Biological evaluation of rapeseed meal, soya-bean meal and casein fed to the weanling and the mature rat

Abstract: I. The biological evaluation of solvent and prepress-solvent processed rapeseed meals KM(S) and RM(PS) was carried out with the weanling (phase I) and the mature (phase z ) rat. The nutritional indices measured were compared with those for diets containing soyabean meal SM and casein CS.2. The true nitrogen digestibility (td(N)) for RM(S), RM(PS), SM and CS in the weanling rat was (%) 78.9 f 1'2,77'9 k 2.7, 90'4f 0.9 and 96.0 If: 0.6 (P < 0.01) respectively. Net protein utilization was (%) 68.9 f 10.1, 65.6f 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…No difference was found within the experimental groups in survival between the 12 and 24% level of protein intake after 12 weeks of dietary treatment. This result is in accord with previous studies that have used similar levels of dietary protein, in that the improved survival of animals on the lower protein intake only became apparent 20 weeks after a reduction in renal mass [3,4], Vegetable proteins generally tend to be of a slightly lower nutritive value than milk proteins, a range of re ported values of 60-90% for soya compared to casein [18][19][20], In this study, animals maintained on soya diets tended in all groups towards a reduced weight gain com pared to their casein counterparts, however, only in groups A and C was this difference significant. Previous studies have shown that so^a protein has a lower true digestibility value than casein (reported range 80-90%) [19,21], with rats ingesting soya protein having lower urinary nitrogen excretion and higher faecal nitrogen excretion, despite both proteins maintaining similar rates of growth.…”
Section: Discussionsupporting
confidence: 81%
“…No difference was found within the experimental groups in survival between the 12 and 24% level of protein intake after 12 weeks of dietary treatment. This result is in accord with previous studies that have used similar levels of dietary protein, in that the improved survival of animals on the lower protein intake only became apparent 20 weeks after a reduction in renal mass [3,4], Vegetable proteins generally tend to be of a slightly lower nutritive value than milk proteins, a range of re ported values of 60-90% for soya compared to casein [18][19][20], In this study, animals maintained on soya diets tended in all groups towards a reduced weight gain com pared to their casein counterparts, however, only in groups A and C was this difference significant. Previous studies have shown that so^a protein has a lower true digestibility value than casein (reported range 80-90%) [19,21], with rats ingesting soya protein having lower urinary nitrogen excretion and higher faecal nitrogen excretion, despite both proteins maintaining similar rates of growth.…”
Section: Discussionsupporting
confidence: 81%
“…The PER of unsupplemented DTP-20 was 2.18 and the NPU 0.55. Values previously reported for SOM-45 byDrouliscos & Bowland (1969) were PER 2-40, NPU 0.80, and the present results gave a PER of 2-20 and 2-94 for the BP-T and CS respectively…”
supporting
confidence: 81%
“…There is impressive evidence that a soyabean-protein diet may be quite effective in ameliorating uraemic symptoms and preventing some of the complications of CRF. Previous studies have shown that soyabean protein has a lower nutritive value compared with casein (Drouliscos & Bowland, 1969). However, soyabean protein is now recognized as a complete protein, using the protein digestibility-corrected amino acid score that has been adopted as an alternative method for evaluating protein quality (Food and Drug Administration, 1991;Young, 1991).…”
Section: Discussionmentioning
confidence: 99%